Race or Resource? BMI, Race, and Other Social Factors as Risk Factors for Interlimb Differences among Overweight Breast Cancer Survivors with Lymphedema - Lorraine T. Dean; Anagha Kumar; Taehoon Kim; Matthew Herling; Justin C. Brown; Zi Zhang; Margaret Evangelisti; Renata Hackley; Jiyoung Kim; Andrea Cheville; Andrea B. Troxel; J. Sanford Schwartz; et al. (Journal of Obesity)
Introduction. High BMI is a risk factor for upper body breast cancer-related lymphedema (BCRL) onset. Black cancer survivors are more likely to have high BMI than White cancer survivors. While observational analyses suggest up to 2.2 times increased risk of BCRL onset for Black breast cancer survivors, no studies have explored race or other social factors that may affect BCRL severity, operationalized by interlimb volume difference (ILD). Materials and Methods. ILD was measured by perometry for 296 overweight (25 > BMI < 50) Black (n=102) or White (n=194) breast cancer survivors (>6 months from treatment) in the WISER Survivor trial. Multivariable linear regression examined associations between social and physical factors and ILD. Results. Neither Black race (−0.26, p=0.89) nor BMI (0.22, p=0.10) was associated with ILD. Attending college (−4.89, p=0.03) was the strongest factor associated with ILD, followed by having more lymph nodes removed (4.75, p=0.01), >25% BCRL care adherence (4.10, p=0.01), and years since treatment (0.55, p<0.001). Discussion. Neither race nor BMI was associated with ILD among overweight cancer survivors. Education, a proxy for resource level, was the strongest factor associated with greater ILD. Tailoring physical activity and weight loss interventions designed to address BCRL severity by resource rather than race should be considered.